The Impact of Human Resources Management Practice amidst COVID-19 - Mobo, Froilan (Future Science / FSH-PH Publications, 2020)
The Novel Corona Virus COVID-19 made a huge impact in most private and government institutions with regards to their Human Resource Management Practices, especially in terms of how employees will work during the time of the pandemic. As per the Inter-Agency Task Force on COVID-19 Philippines there is a need to observe Social Distance and proper quarantine protocol to avoid from the infections of the widespread virus. The Civil Service Commission Philippines and the other government agencies release a memorandum on the operational process of manpower during the pandemic situations. As a result of their discussion they have come-up with a new approach with regards to operational procedures on Human Resources. Most of the Human Resource Management Officer arranged a Work From Home Scheme while others on a 50% capacity of manpower to report for work depending on the quarantine protocol set by regions or provinces. New Best Practices will be applied in the coming New Nor-mal in terms of Human Resources Management Approach.